2015
DOI: 10.1200/jop.2014.000034
|View full text |Cite
|
Sign up to set email alerts
|

Breast Cancer Stage and Treatment Among Ohio Medicaid Beneficiaries With and Without Mental Illness

Abstract: Among Ohio Medicaid beneficiaries, women with mental illness did not experience disparities in breast cancer stage or treatment of locoregional disease. These findings may reflect the equalizing effects of Medicaid through vulnerable individuals' improved access to both physical and mental health care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 38 publications
0
6
1
Order By: Relevance
“…Our findings are consistent with increased unadjusted rates of advanced disease reported in previous population studies, [15][16][17][18][19] suggesting that previous findings are not merely due to differences in demographics or screening participation. Our findings contrast with those of Koroukian et al, 23 who found a lower adjusted risk of advanced disease in women accessing MH services. The authors of that study speculated that their findings may have reflected the use of a comparison group who had significant health and social problems (women accessing US Medicaid services for non-MH conditions).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Our findings are consistent with increased unadjusted rates of advanced disease reported in previous population studies, [15][16][17][18][19] suggesting that previous findings are not merely due to differences in demographics or screening participation. Our findings contrast with those of Koroukian et al, 23 who found a lower adjusted risk of advanced disease in women accessing MH services. The authors of that study speculated that their findings may have reflected the use of a comparison group who had significant health and social problems (women accessing US Medicaid services for non-MH conditions).…”
Section: Discussioncontrasting
confidence: 99%
“…17 However, these studies have not adjusted for factors such as age, socioeconomic disadvantage, or rural residence that may influence both screening participation 20 and degree of spread, [20][21][22] and also covary with mental health conditions. Only one study 23 has compared breast cancer stage in women with mental illness after adjusting for these factors, unexpectedly finding that women using US Medicaid MH services had a lower adjusted rate of distant stage cancer (hazard ratio, 0.59) than women who had received other Medicaid services. To our knowledge, no study has examined both breast cancer screening participation rates and degree of cancer spread at diagnosis in women with MH conditions to assess directly how screening participation contributes to possible differences in cancer stage at presentation and hence subsequent differences in mortality.…”
Section: Introductionmentioning
confidence: 99%
“…The role of mental health is gaining greater prominence in outcomes research; and increasingly, recent studies are investigating cancer-related outcomes (1,2), including cancer screening, stage at diagnosis, receipt of treatment, and survival, in the presence of comorbid mental conditions. Prior studies have documented excess cancer mortality in people with mental illness (3,4).…”
mentioning
confidence: 99%
“…We used data from the Ohio Cancer Incidence Surveillance System (OCISS) and Ohio Medicaid enrollment data, which we linked using a deterministic linkage algorithm based on the patient's social security number, first and last name, date of birth, and sex. [17][18][19][20]29 Further contextual data were derived from the 2013-2017 American Community Survey data from the US Census (income, education, and percent uninsured at the census tract level; urbanicity/rurality of patients' county of residence) and the Health Resources Service Administration to identify Health Professional Shortage Areas (HPSAs).…”
Section: Data and Study Samplementioning
confidence: 99%